2018
DOI: 10.1186/s13756-018-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospitalized patients with resistant or multidrug-resistant Pseudomonas aeruginosa infections: a systematic review and meta-analysis

Abstract: BackgroundIdentifying risk factors predicting acquisition of resistant Pseudomonas aeruginosa will aid surveillance and diagnostic initiatives and can be crucial in early and appropriate antibiotic therapy. We conducted a systematic review examining risk factors of acquisition of resistant P. aeruginosa among hospitalized patients.MethodsMEDLINE®, EMBASE®, and Cochrane Central were searched between 2000 and 2016 for studies examining independent risk factors associated with acquisition of resistant P. aerugino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
118
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 65 publications
19
118
1
7
Order By: Relevance
“…This might be due to variation in sample size, clinical site of infection, age of patients, hospital setting, duration of hospitalization, patients exposure to high risk devices or surgical procedures, microbiological methods employed for screening of MDR resistant strains. The highest proportion of MDR non-fermentative gram negative bacilli NI infection among the lower age groups in the present study is consistent with earlier studies elsewhere in the world [29,33,34]. On the other hand, in the present study all NIs observed among patients with intravenous catheterization.…”
Section: Discussionsupporting
confidence: 93%
“…This might be due to variation in sample size, clinical site of infection, age of patients, hospital setting, duration of hospitalization, patients exposure to high risk devices or surgical procedures, microbiological methods employed for screening of MDR resistant strains. The highest proportion of MDR non-fermentative gram negative bacilli NI infection among the lower age groups in the present study is consistent with earlier studies elsewhere in the world [29,33,34]. On the other hand, in the present study all NIs observed among patients with intravenous catheterization.…”
Section: Discussionsupporting
confidence: 93%
“…age groups in the present study is consistent with earlier studies elsewhere in the world [29,33,34].…”
Section: The Highest Proportion Of Mdr Non-fermentative Gram Negativesupporting
confidence: 93%
“…Additionally, this review comprehensively searched for studies indexed in regional databases. The overall results from this review are consistent with other systematic reviews published literature from other regions that compare the role of AIAT with IIAT in mortality [8,35,36]. Nonetheless, in light of a few limitations, the results of the systematic review and metaanalysis should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 85%